Prediction of acute poisoning in agricultural workers during using pesticides on berry and melon crops - Olha Bilous; Olena Vavrinevych (Ukrainian Scientific Medical Youth Journal, 2022)
acute pesticide poisoning is a global health problem. According to the WHO, poisoning by chemicals, including chemical plant protection products, is a leading non-communicable disease. Violation of the rules for working with pesticides leads to the occurrence of occupational diseases among workers. Therefore, compliance with pesticide regulations and the use of personal protective equipment is a very important preventive measure. The purpose of our work: to predict the occurrence of acute toxic effects in workers who treat berry and melon crops with pesticides. Research materials and methods: to assess the probability of acute toxic effects among workers who deal with active substances and preparations based on them. We calculated three indicators: the coefficient of possible inhalation poisoning (DSanPiN 8.8.1.002-98), the selectivity of pesticides by inhalation pesticides and the selectivity of pesticides under dermal exposure according to the method of Sergeeva S.G. Results: according to the "Hygienic classification of pesticides by degree of danger" DSanPiN 8.8.1.002-98 all tested active substances belong to the 4th class of danger according to the coefficient of possible inhalation poisoning, which was less than 0,5. The coefficient of selectivity of the action of pesticides during inhalation exposure to active substances was in the range of 7,41 – 1000,0. For cyprodinil, phenhexamid, azoxystrobin, pyraclostrobin, copper chloride, pendimethalin, S-metolachlor, glyphosate, and abamectin, it was less than 100, indicating their relatively low selectivity of action. Other studied active substances had a high selectivity of action, since this coefficient was more than 100. It was established that all studied drugs have sufficient selectivity of action when inhaled. The coefficient of selectivity for dermal exposure was more than 100 for all the studied active substances, except for S-metolachlor and glyphosate. Preparations Trinol, VG, Signum, VG, Ridomil Gold R 161 WG, VG, Stomp Aqua, SK, Dual Gold 960 EC, KE, Herbolex v.r. have low selectivity of action when entering through the skin, all other pesticides have sufficient selectivity of action. The obtained data indicate that all the active substances under study are not dangerous (hazard class 4), according to DSanPiN 8.8.1.002-98. Therefore, when working with these substances you need to follow hygienic regulations.